PENGARUH PEMBERIAN INFORMASI OBAT TERHADAP TINGKAT KEPATUHAN PENGGUNAAN ANTIBIOTIKA PADA PASIEN PNEUMONIA DI RS PKU MUHAMMADIYAH GUBUG - Triana Aprilyya; Zaenal Fanani; Galih Kurniawan (Nusantara Hasana Journal, 2025)
Pneumonia is a lower respiratory tract infection that remains a major cause of morbidity and mortality, especially in developing countries like Indonesia. The success of pneumonia therapy depends heavily on patient compliance in using antibiotics appropriately. However, patient compliance with antibiotic treatment remains low, which risks relapse and antibiotic resistance. One important factor that can improve understanding is presenting drug information accurately and clearly. This study aims to determine the effect of providing drug information on the level of antibiotic compliance in pneumonia patients at PKU Muhammadiyah Gubug Hospital. This study used a quasi-experimental method with a non-equivalent control group design, involving two groups of pneumonia patients: those before and after receiving drug information intervention using leaflets. Compliance levels were measured using the MARS (Medication Adherence Rating Scale) questionnaire before and after the intervention. The results of the study will compare the significance of antibiotic compliance levels in the pre- and post-intervention groups (p < 0.05) using the Wilcoxon Signed Rank Test. Patients who were provided with information showed a better understanding of the importance of completing antibiotic therapy as recommended. In conclusion, providing effective drug information can improve patient adherence to antibiotic use, contributing to successful therapy and preventing resistance. These results can serve as a basis for developing drug information intervention programs in hospitals